Genetic diversity of green turtle (chelonia mydas) from Talang-Talang Island and Satang Island, Sarawak based on coi gene analysis - Nursyuhaida, Md Shahid (Universiti Malaysia Sarawak (UNIMAS), 2011)
Chelonia mydas (green turtle) is a long lived marine reptile with complex life histories that is extensively distributed across the globe and has become the quintessential subject for public conservation awareness. Many studies on C.mydas from Sarawak had been carried out in terms of population size, tagging experiment in assessing turtle migration and study on green turtle egg hatch rate. Several preliminary molecular works on C.mydas using D-Loop and 16S gene sequences had also been conducted. However, there is no study yet conducted on C.mydas from Sarawak, using Cytochrome Oxidase I (COI) gene sequence. Therefore, this study is aimed to sequence COI gene from C.mydas of Satang Island and Talang-Talang Island and the sequence data will be used to assess genetic variation between individuals and infer molecular phylogeny of C.mydas. This study involved the utilization of molecular work involving total genomic DNA extraction, Polymerase Chain Reaction, DNA sequencing and Phylogenetic Analysis. A total of 510bp of COI gene sequences were obtained from C.mydas in this study. Genetic divergence of 0% to 0.2% was recorded among C.mydas samples from both study sites indicating intraspecific variations between C.mydas samples. Phylogenetic trees constructed showed monophyletic of the C.mydas samples as they grouped together into a single clade.